Particles size and conductivity study of P-Type copper (I) iodide (CUI) thin film for solid state dye-sensitized solar cells - Ayib Rosdi, Zainun; M. H., Mamat; U. M., Noor; R., Yusop (IOP Publishing, 2011)
Copper Iodide based dye-sensitized solar cells (DSSC) has been reported either deliver small photocurrents or highly unstable. In this research, by added in a small amount of Tetra-methyl-ethylene-diamine (TMED) into CuI sol-gel (CuI in acetonitrile), performance of electrical properties and optical properties of CuI based DSSC have been studied. Particles size and conductivity of CuI solution were measured when addition of TMED to the sol at 0.05M concentrations. Spin-coating technique has been explored to prepare nano-crystalline CuI films at room temperature. The film was examined for their surface morphology, optical and electrical properties by field emission scanning electron microscope (FESEM), ultraviolet visible spectroscopy (UV-Vis), Photoluminescence (PL) and current-voltage (I-V) measurement respectively. The results were then compared with CuI sol-gel which prepared by dissolving CuI powder with acetonitrile only. It showed some improvement to the CuI-based DSSC by incorporation of a small quantity of TMED in the solution of precursor.